Small RNA Profiling in Dengue Virus 2-Infected Aedes Mosquito Cells Reveals Viral piRNAs and Novel Host miRNAs. - Pascal Miesen; Alasdair Ivens; Amy H Buck; Ronald P van Rij (Public Library of Science (PLoS), 2016)
In Aedes mosquitoes, infections with arthropod-borne viruses (arboviruses) trigger or modulate the expression of various classes of viral and host-derived small RNAs, including small interfering RNAs (siRNAs), PIWI interacting RNAs (piRNAs), and microRNAs (miRNAs). Viral siRNAs are at the core of the antiviral RNA interference machinery, one of the key pathways that limit virus replication in invertebrates. Besides siRNAs, Aedes mosquitoes and cells derived from these insects produce arbovirus-derived piRNAs, the best studied examples being viruses from the Togaviridae or Bunyaviridae families. Host miRNAs modulate the expression of a large number of genes and their levels may change in response to viral infections. In addition, some viruses, mostly with a DNA genome, express their own miRNAs to regulate host and viral gene expression. Here, we perform a comprehensive analysis of both viral and host-derived small RNAs in Aedes aegypti Aag2 cells infected with dengue virus 2 (DENV), a member of the Flaviviridae family. Aag2 cells are competent in producing all three types of small RNAs and provide a powerful tool to explore the crosstalk between arboviral infection and the distinct RNA silencing pathways. Interestingly, besides the well-characterized DENV-derived siRNAs, a specific population of viral piRNAs was identified in infected Aag2 cells. Knockdown of Piwi5, Ago3 and, to a lesser extent, Piwi6 results in reduction of vpiRNA levels, providing the first genetic evidence that Aedes PIWI proteins produce DENV-derived small RNAs. In contrast, we do not find convincing evidence for the production of virus-derived miRNAs. Neither do we find that host miRNA expression is strongly changed upon DENV2 infection. Finally, our deep-sequencing analyses detect 30 novel Aedes miRNAs, complementing the repertoire of regulatory small RNAs in this important vector species.